Optimization of credit portfolio by evolutionary algorithm - Yan, Ran (2009)
During the past few decades, one of the most important advances in the investment field has been the creation of an optimum investment portfolio with desirable risk-return characteristics. The basic portfolio model was developed by Harry Markowitz, who derived the expected rate of return for a portfolio of assets and showed that the variance of the rate of return was a meaningful measure of portfolio risk. This portfolio variance formula not only indicated the importance of diversifying investments to reduce the total risk of a portfolio but also showed how to effectively diversify out the risks. Capital market theory extends portfolio theory and develops a model for pricing all risky assets. The final product, the Capital Asset Pricing Model (CAPM), will allow the investor to determine the required rate of return for any risky asset.